Residents' attitudes toward impacts of tourism: A case study of Langkawi, Malaysia - Mohd Shariff, Nurhazani; Tahir, Shaharuddin (Universiti Utara Malaysia, 2003)
This paper presents findings from a study that was undertaken to investigate residents’ attitudes toward the impacts of tourism in Langkawi Island, Malaysia. In order to gain reliable results for the use of Langkawi policy makers and tourism planners, a standardized instrument for measuring residents’ attitude was developed and used in the study. The findings revealed that residents tend to perceive impacts that benefit them as positive impacts of tourism. The findings also indicated that residents tend to perceive impacts of tourism, either positively or negatively depending on how much they would affect their personal lives. The more dependent they were on the positive impacts of tourism, the more supportive they were toward tourism development. Thus, the findings do not support Doxey’s Irridex Model. Finally, the study suggested that for a long-term purpose of achieving sustainable tourism development, Langkawi tourism planners and policy makers should conduct several campaigns and tourism workshops for the residents. Accordingly, this would gain residents support for tourism development on the island.